Feeling dark, seeing dark: Mind–body in dark tourism. (January 2021) - Sun, Jiaojiao; Lv, Xingyang
Abstract: Embodiment is a key under-researched component of dark tourism experiences. Qualitative and experimental methods were applied in four studies to reveal the bidirectional body–mind synchronization in dark tourism experiences. Taking the Chernobyl zone as a case, we first prove the mind-to-body pathway in which the dark experience exerts a measurable effect on the participants' sensory expression in photographs and sketches. We then discover the body-to-mind pathway in which the expressions of darkness can be decoded by others. Furthermore, this study illustrates how the different dark levels of the product photos on a website affect the potential tourists' feelings. This study expands the understanding of embodiment theory in dark tourism with implications for product design and marketing. Graphical abstract: Unlabelled Image Highlights: The bidirectional body–mind synchronization is constructed in dark tourism. Dark experience influences sensory expression in photographs and sketches. The expressions of darkness can be decoded and correctly interpreted by others. Different dark levels of photos affect the potential tourists' product evaluation.